HUMAN CAPITAL AND INNOVATION IN A MONETARY SCHUMPETERIAN GROWTH MODEL. (10th August 2017) - Chu, Angus C.; Ning, Lei; Zhu, Dongming
Abstract : This study explores the growth and welfare effects of monetary policy in a scale-invariant Schumpeterian growth model with endogenous human capital accumulation. We model money demand via a cash-in-advance (CIA) constraint on research and development (R&D) investment. Our results can be summarized as follows. We find that an increase in the nominal interest rate leads to a decrease in R&D and human capital investment, which, in turn, reduces the long-run growth rates of technology and output. This result stands in stark contrast to the case of exogenous human capital accumulation in which the long-run growth rates of technology and output are independent of the nominal interest rate. Simulating the transitional dynamics, we find that the additional long-run growth effect under endogenous human capital accumulation amplifies the welfare effect of monetary policy. Decreasing the nominal interest rate from 10% to 0% leads to a welfare gain that is equivalent to a permanent increase in consumption of 2.82% (2.38%) under endogenous (exogenous) human capital accumulation.